The Influence Of Net Profit Margin, Working Capital Turnover, Debt To Equity Ratio, And Total Asset Turnover On Profit Growth - Astrid Dita Meirina Hakim; Ahmad Romi Kurniawan Ardianto; Imam Tri Wibowo (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of Net Profit Margin (NPM), Working Capital Turnover (WCTO), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Profit Growth in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The research employs a quantitative approach using secondary data derived from audited financial reports. Sampling was conducted using purposive sampling, resulting in 15 companies that met the criteria. Data were analyzed using panel data regression with the help of EViews 12 software. The classical assumption tests confirmed that the data met normality, multicollinearity, autocorrelation, and heteroscedasticity requirements. The findings revealed that DER has a positive and significant effect on profit growth, while NPM, WCTO, and TATO showed no significant influence. These results suggest that effective management of capital structure, particularly through optimized use of debt, contributes meaningfully to enhancing company profits. Meanwhile, profitability, working capital efficiency, and asset utilization alone do not guarantee growth in earnings within the capital-intensive and volatile energy sector. This study contributes to the understanding of financial performance drivers in the energy industry and offers practical insights for investors, managers, and academics in financial decision-making.